Diversion layer and preparation process and system thereof
By adopting a double-layer fiber mesh structure and low-pressure hydrospunlace hot air consolidation process, an asymmetric structure with obvious pore differences is formed, and a water droplet-shaped protrusion is formed on the surface of the fiber mesh, which solves the problems of fiber slippage and pore structure deformation of the guide layer, and significantly improves the permeability and diffusion performance of the guide layer.
Patent Information
- Application Number
- CN202411655857.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-19
AI Technical Summary
During the use of existing hot air guide material, the capillary force is weakened due to fiber slippage and pore structure deformation, which affects the rapid infiltration of liquid and the reduction of re-seepage amount.
A bilayer fiber web structure is adopted, in which the non-used surface fiber web consists of two-component orange petal fibers and non-hot melt fibers with hygroscopicity. A non-symmetric structure with obvious pore differences is formed through low-pressure hydrospuncture and hot air consolidation processes, and water droplet-shaped protrusions are formed on the surface of the fiber web to enhance the capillary effect.
The permeability rate and diffusion effect of the diversion layer are significantly improved, ensuring the pore structure retention and capillary force stability of the diversion layer under arc surface conditions, thereby improving the rapid infiltration of liquid and the reduction of re-seepage amount.
Smart Images

Figure CN119567667A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flow-guiding layer for sanitary products and a preparation process and system thereof. Background Art
[0002] At present, the hot air diversion layer material has the problem of large differences in the number of consolidation points and flatness between the use surface (contact surface with the support net curtain) and the non-use surface of the fiber, and low pore structure strength. In the actual use scenario of sanitary napkins, the diversion layer will be bent into an arc. Since there are fewer consolidation points between the fibers on the non-use surface, the ability to resist deformation is weaker, and the fibers are more likely to slip. After the fiber slips, the pore structure of the diversion layer will be deformed, and the contact points between the fibers will decrease, thereby increasing the equivalent pore size of the non-use surface of the diversion layer and weakening the capillary force, which is not conducive to the rapid infiltration of liquid and the reduction of back infiltration.
[0003] Since the pure cotton surface layer has higher requirements on the penetration rate and back-infiltration volume under the drainage layer, a stronger capillary effect is needed to improve the performance of the drainage layer.
[0004] For single-layer guide layer materials, coarse denier fibers and fine denier fibers can be mixed to form a two-layer structure with different pores. Patent CN203436464U introduces a guide layer with an upper and lower layer structure. The upper layer is a longitudinally combed fiber layer, which is used to disperse the liquid longitudinally, and the lower layer is a transverse fiber layer, which quickly absorbs the liquid to prevent reverse osmosis. However, the pore difference of this method is not obvious enough. Usually, the ratio of the upper and lower pore sizes is within 10 times, which has limited improvement on the performance of the guide layer.
[0005] Using two fiber webs with different wettability to form a differential capillary effect through hot air consolidation can achieve unidirectional water conduction of the material and improve the performance of the guide layer. For example, patent CN 117779347 A introduces a directional moisture-conducting nonwoven fabric and its preparation method and disposable sanitary products, which have the characteristics of small surface diffusion, shielding menstrual blood, rapid liquid infiltration, and low rewetting. However, the differential capillary effect formed by the difference in wettability has a certain resistance in the liquid infiltration process, which reduces the absorption speed of the guide layer.
[0006] For the guide layer composed of multiple layers of materials, the composite process can easily destroy the pore structure of the hot air cloth, and there are large gaps between the composites, which cannot fit tightly, and the performance is far worse than that of the one-piece formed guide layer material. Summary of the invention
[0007] In order to overcome the above-mentioned defects, the object of the present invention is to provide a new type of guide layer and its preparation process.
[0008] In order to achieve the above-mentioned purpose, the guide layer of the present invention is composed of a double-layer fiber mesh, wherein:
[0009] The weight of the guide layer is 30-60g / m2 The non-use surface fiber mesh weight is 18-36g / m 2 The surface fiber mesh weight is 12-24g / m 2 ;
[0010] The thickness of the guide layer is 0.8-1.6 mm, and the thickness ratio of the fiber mesh on the use surface to the fiber mesh on the non-use surface is 1:2-4;
[0011] The non-use surface fibers are composed of bicomponent orange segment fibers and non-thermal-melting fibers with hygroscopicity.
[0012] Furthermore, the bicomponent pie-shaped fiber is PA6 and low melting point PET, with a denier of 3D to 6D, a length of 10-50mm, a number of pieces of 6 to 32, and a fineness of 0.05-1D after fiber opening.
[0013] Furthermore, water drop-shaped protrusions are formed on the lower surface of the fiber web on the use side and / or the fiber web on the non-use side, and the diameter of the water drop-shaped protrusions is 0.001-0.1 mm; the number of the water drop-shaped protrusions is 10-1000 / cm 2 .
[0014] In order to achieve the above object, the preparation process of the guide layer of the present invention comprises the following steps:
[0015] 1) Opening, combing and laying the fiber webs on the use side and the non-use side; wherein the fiber web on the non-use side is laid directly to ensure that the fiber longitudinal orientation is high and the fibers are more dense, which is conducive to longitudinal diffusion;
[0016] 2) Perform two rounds of drum hydroentanglement reinforcement on the non-use surface fiber web. The pressure of the first and second hydroentanglement processes are 10-20 bar and 30-40 bar respectively, and each hydroentanglement process is equipped with 1-6 hydroentanglement heads; the mesh number of the drum mesh curtain 1 is 60-80 mesh, and the mesh curtain 2 is 10-30 mesh, and a pressing roller is provided after the hydroentanglement reinforcement to remove the retained water in the fiber web.
[0017] 3) Alkali treatment of the non-use surface fiber layer.
[0018] 5. The process for preparing the guide layer according to claim 4, characterized in that it further comprises the following steps:
[0019] Water drop-shaped protrusions are prepared on the lower surface of the fiber web on the use surface and / or the non-use surface, wherein the diameter of the water drop-shaped protrusions is 0.001-0.1 mm; and the number of the water drop-shaped protrusions is 10-1000 / cm 2 .
[0020] Furthermore, the method further comprises the following steps: the step of preparing the water drop-shaped protrusion comprises:
[0021] Atomized finishing liquid is prepared; the atomized finishing liquid consists of a hydrophilic oil agent, a binder and water.
[0022] Using an atomizing device to spray droplets of atomized finishing liquid onto the surface of the fiber web;
[0023] At the same time, the suction device is used to attach to the fiber surface to achieve a single-sided finishing effect;
[0024] Using the hot air flow to change the viscosity of the atomized droplets is conducive to forming a water droplet structure;
[0025] Hot air is used to pre-consolidate the fibers while allowing the atomized droplets to solidify on the fiber web surface in the form of water droplets.
[0026] To achieve the above-mentioned purpose, the system for preparing the flow guide layer of the present invention at least comprises a system for preparing the non-use surface fiber web; the system for preparing the non-use surface fiber web comprises: a carding machine; a web laying machine; a first drum net curtain; a first water spunlace; a pressure roller; an alkali treatment device; a washing device; a second drum net curtain; a second water spunlace; an atomizing device; a holding airflow jet device; a suction device; and a hot air reinforcement oven; wherein,
[0027] 1) The non-use surface fiber web is opened and combed by a carding machine;
[0028] The net is laid by a net laying machine;
[0029] The laid fiber web passes through the drum screen for the first hydroentanglement;
[0030] After the first spunlacing process, the non-use surface fiber web is squeezed by a pressing roller and then enters the alkali treatment equipment;
[0031] After the alkali treatment, the non-use surface fiber web is squeezed by a pressing roller and then enters the washing equipment;
[0032] After washing, the non-use surface fiber web is squeezed by a pressure roller and passed through a rotary drum screen for the second hydroentanglement.
[0033] 2) The surface fiber web is opened and combed, and there is no need to lay the web, and it can be directly atomized and hot-air consolidated;
[0034] Use a surface fiber net to perform surface atomization through an atomization device;
[0035] After being shaped by the holding air jet device and the suction device, it enters the hot air consolidation oven for consolidation;
[0036] 3) Integrating the non-use surface fiber web processed in step 1) and the use surface fiber web processed in step 2).
[0037] The beneficial effects of the present invention are:
[0038] 1. The surface of the guide layer penetrates quickly, and the bottom layer has a large diffusion area. ES fibers of different deniers are used, combined with low-melting-point PET and PA6 bicomponent orange-segment fibers and hygroscopic non-thermal-melting fibers. Through a special low-pressure hydroentanglement and hot air consolidation process, an asymmetric structure with a pore difference of more than 10 times is constructed, which greatly improves the penetration speed, and utilizes the synergistic effect of the capillary force formed by the hydrophilic groups and the micropores on the fibers and the capillary force formed by the pores between the fibers to improve the diffusion effect of the liquid in the bottom layer.
[0039] 2. Through the combination of low-pressure water spunlace and hot air technology, the fibers at the interface of the surface and bottom fiber webs are entangled with each other to form a pore structure in a transitional state, forming a gradient structure to improve the capillary force weakening phenomenon caused by the sudden change of 10 orders of magnitude in the pore structure.
[0040] 3. The number of consolidation points between fibers in the guide layer is large, and the pore structure has high strength. Under the conditions of simulating the actual arc surface, the pore structure has good shape retention, the capillary force changes little, and the guide effect is better. The previous hydroentanglement process allows the fibers to bend and entangle to produce contact points, thereby forming more bonding points between the cortexes under the action of hot air flow.
[0041] 4. The guide layer has good flatness, and the surface and bottom layers are basically free of hairiness. The reinforcement effect of the water needle impacting the upper fiber mesh, combined with the support of the hot air curtain on the lower fiber mesh, the use surface and the non-use surface have high flatness and less hairiness.
[0042] 5. The low-pressure hydroentanglement and hot air consolidation process solves the problem of hydrophilic oil loss caused by high-pressure water needles impacting the hot air fiber surface in the traditional hydroentanglement process, and breaks through the bottleneck of the hot air consolidation process that cannot use high-content non-hot-melt fibers. Compared with the hydroentanglement process, the required hydroentanglement pressure is small, and no drying is required after hydroentanglement. Compared with the hot air process, there will be no obvious difference in flatness between the use surface and the non-use surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The schematic diagram of the preparation device of the guide layer of the present invention is shown in FIG.
[0044] Figure 2 This is the schematic diagram of the spunlace plate.
[0045] Figure 3 for Figure 2 main view.
[0046] Figure 4 This is the test result of the aperture tester.
[0047] Description of the figure number:
[0048] 1- non-use surface fiber web; 2- combing machine 1; 3- web laying machine; 4- drum mesh curtain 1; 5- front-end airflow reinforcement and water needle reinforcement; 6-1, 6-2, 6-3, 6-4 pressure rollers; 7-1 alkali treatment; 7-2 water washing; 8- use surface fiber web; 9- combing machine 2; 10- drum mesh curtain 2; 11- back-end water spunlace; 13-1 atomizing device 13-2 holding airflow jet device; 13-3 holding hot airflow; 13-4 suction device; 13-5 atomizing small droplets; 14- hot air reinforcement oven. DETAILED DESCRIPTION
[0049] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0050] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0051] Example 1
[0052] The present invention involves constructing an integrated asymmetric structure with obvious pore differences in the guide layer, optimizing the competitive relationship between liquid penetration and diffusion in the guide layer, and the upper layer penetrates quickly and the bottom layer diffuses quickly. First, after the liquid contacts the guide layer, the penetration process is dominant. For penetration to be dominant, there must be a sufficient capillary pressure difference ΔP (as shown in Formula 1). In the formula, θ1 and θ2 are the contact angles of the non-use surface and the use surface, respectively, γ is the surface tension of the liquid in the air, and D1 and D2 are the average equivalent diameters of the capillary channels of the non-use surface and the use surface, respectively. In the present invention, by combining low-pressure water spurting with hot air consolidation technology, it is ensured that the contact angles of the use surface and the non-use surface are both hydrophilic (i.e., θ1, θ2 < 90°, cosθ > 0), and D1 < D2, D2 / D1 ≥ 10, thereby greatly improving the capillary pressure difference ΔP, so that the liquid can be quickly and directionally conducted from the large pore structure to the small pore structure under the capillary pressure difference.
[0053] When the liquid penetrates into the lower layer, the diffusion effect is dominant and the capillary force P of the bottom layer needs to be large enough (as shown in Formula 2). The traditional hot air guide layer mainly uses the pore structure formed between fibers to form capillary action. The present invention adds hygroscopic non-thermofusible fibers and uses the synergistic effect between the capillary force P1 formed by the hydrophilic groups and the micropores on the fibers and the capillary force P2 formed by the pores between the fibers to further enhance the diffusion of the liquid in the bottom layer, thereby achieving rapid diffusion of the liquid on the lower fiber web.
[0054]
[0055] P=P1+P2 Formula 2
[0056] This embodiment provides a method for preparing the above-mentioned 40g / ㎡ flow-guiding layer, comprising the following steps: the surface fiber web has a gram weight of 24g / m 2 The weight of the bottom fiber web is 16g / m 2 The thickness ratio of the surface fiber web to the bottom fiber web is approximately 1:3.
[0057] (1) Prepare the raw materials. The non-use side fiber is orange-peel type bicomponent fiber and viscose fiber. The orange-peel type bicomponent fiber has a denier of 3D and 16 petals. The use side fiber web core type bicomponent ES fiber has a denier of 6D and 12D, and a length of 50 mm. The two fibers on the non-use side are evenly mixed and combed, and the orange-peel type bicomponent fiber: viscose fiber = 1:8. The two fibers on the use side are evenly mixed and combed, and the hydrophilic coarse denier ES fiber: hydrophilic medium denier ES fiber (weight ratio) = 1:8.
[0058] (2) Hydroentanglement. Hydroentanglement is performed by a rotary screen hydroentanglement process. The upper fiber web is pre-wetted and then hydroentangled under the transport of mesh curtain 1, which is a 60-mesh mesh curtain. After hydroentanglement, a pressure roller is provided to remove the retained water in the fiber web. The first hydroentanglement process is provided with two hydroentanglement heads. The first hydroentanglement head is for front-side reinforcement, and the pressure of the hydroentanglement head is 15 bar. The second hydroentanglement head is for reverse-side reinforcement, and the pressure of the hydroentanglement head is 20 bar.
[0059] (3) Alkali treatment of the non-use surface fiber layer. After the previous hydroentanglement reinforcement, the fiber web is treated in an alkaline solution and then washed with water. The concentration of the alkaline solution is 5g / L, the bath ratio is 1:20, and the temperature is 80℃.
[0060] (4) Second hydroentanglement. The fiber web of the lower layer does not need to be pre-wetted. The fiber web of the upper layer and the fiber web of the lower layer are supported by the mesh curtain 2 and go through the second hydroentanglement together. The mesh curtain 2 is a 10-mesh mesh curtain. The second hydroentanglement process is equipped with two hydroentanglement heads with pressures of 30 bar and 40 bar, and both are equipped with pressure rollers to remove the retained water in the fiber web.
[0061] (5) Hot air consolidation: The drying temperature is 130-150°C and the drying speed is 40 m / min.
[0062] Comparative Example 1: Double combing is used to prepare the hot air guide layer material, with a gram weight of 40g / ㎡, the non-use surface fiber is 3D skin-core bicomponent ES fiber, and the lower fiber web has a gram weight of 16g / m 2 The surface is made of 6D skin-core two-component ES fiber.
[0063] Comparative Example 2: The rest is the same as Example 1, except that the pressure of the first water jet is 80 bar and 85 bar; the pressure of the second water jet is 90 bar and 100 bar. The mesh curtains of the water jet are all plain mesh curtains, and the high-pressure water jet is combined with a low mesh number, which makes it easy to form a mesh structure on the guide surface.
[0064] Comparative Example 3: The rest is the same as Example 1, except that the non-surface fiber in Comparative Example 3 is a sheath-core bicomponent ES fiber.
[0065] The aperture size and distribution of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were tested using an aperture tester (CFP-1100-AI) produced by PMI, USA. The size of the tested sample was 3×3 cm. 2 , the test environment temperature and humidity were controlled at 20±2℃ and 65%±4% respectively. The test results are as follows Figure 4 As can be seen, the horizontal axis value in the legend represents a pore size range, such as 10 microns represents a pore size range of 0-10 microns, and 20 microns represents a pore size range of 10-20 microns.
[0066] From the pore size distribution curve of Example 1, the pore size of the guide layer of Example 1 is mainly distributed below 10 microns, 10-20 microns, and 140-150 microns. The guide layer of the present invention has obvious pore differences. From the pore size distribution curve of Comparative Example 1, the pores of the hot air guide layer are relatively large, the pores are mainly distributed above 70 microns, and there is no obvious pore difference. From the pore size distribution curve of Comparative Example 2, high-pressure water spunlace will make the fibers entangled more tightly and produce a higher proportion of small pores. From the pore size distribution curve of Comparative Example 3, below 10 microns, the proportion of pores of 10-20 microns is less distributed, the pores are mainly distributed in 40-70 microns, 140-150 microns, and the pore difference becomes smaller. The non-use surface uses non-hot-melt fibers and orange-peel type bicomponent fibers, combined with low-pressure water spunlace hot air process, to form a pore difference of more than 10 times the order of magnitude.
[0067] The absorption performance of the guide layer of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 was tested according to the following method:
[0068] 1. Adjust the temperature of pig blood to 23±1℃;
[0069] 2. Test the thickness of each sample separately;
[0070] 3. Take a sample and place it on the curved sample holder of the absorption rate meter. The absorption rate meter is the instrument required by GBT / 8939-2018 Sanitary Napkin Pads. The sample is backed with 15 layers of absorbent paper, with a quantitative of (145 ± 5) g / m 2 , liquid absorption is greater than 480% (determined according to GB / T24218.6). Place the standard test module above the sample;
[0071] 3. Use a pipette to put 5 ml of pig blood into the standard test module, and start timing the time required for the pig blood to be completely absorbed by the surface layer (i.e., absorption time s);
[0072] 4. After 5 minutes, cover the liquid adding point with filter paper of known weight and place a 5kg arc-shaped pressure block (consistent with the arc of the standard test module). After 2 minutes, weigh the weight W2 of the filter paper and calculate the increased weight of the filter paper (i.e. the back-seepage amount W).
[0073] 5. Repeat step 3 again after 1 minute. Repeat 2 times for a total of 3 times of adding liquid.
[0074] 6. Test the thickness of each sample after adding liquid three times.
[0075]
[0076] Compared with Example 1, Example 1 has a faster absorption speed on the curved surface and a lower amount of back seepage on the curved surface. The performance changes little after multiple liquid additions, indicating that Example 1 has good pore structure shape retention on the curved surface and small changes in capillary force, while Comparative Example 1 has low pore structure strength, which causes fiber slippage and deformation of the pore structure of the guide layer after multiple liquid additions and pressurization, and reduces the number of contact points between fibers, thereby increasing the equivalent pore size of the non-use surface of the guide layer and weakening the capillary force, which is not conducive to rapid liquid infiltration and reduction of back seepage.
[0077] Compared with Example 1 and Comparative Example 2, the absorption speed of Comparative Example 2 is slow and the rewetting amount is higher. Comparative Example 2 uses high-pressure water injection, the fibers are tightly entangled and the pore gradient cannot be formed. At the same time, the high-pressure water injection causes the hydrophilic oil agent on the surface of the ES fiber to be lost.
[0078] Comparing Example 1 with Comparative Example 3, the absorption speed of Comparative Example 3 is slow, and the rewetting amount is similar. Comparative Example 3 does not use orange segment type bicomponent fiber and non-thermofusible fiber with hygroscopicity, and the absorption speed is slightly slower. The pore structure strength of the low-pressure hydroentanglement diversion layer is high. Under the conditions of the curved surface simulated in actual use, the pore structure has good shape retention, the capillary force changes little, and the diversion effect is better.
[0079] Example 1, Comparative Example 1 and Comparative Example 3 were used as the guide layer materials of sanitary napkins, the surface layer was 100% cotton surface layer, and the core was a polymer wood pulp core. The performance of the sanitary napkins was tested according to the following method:
[0080] 1. Adjust the temperature of pig blood to 23±1℃;
[0081] 2. Take a sample and place it on the curved sample holder of the absorption rate meter. The absorption rate meter is the instrument required by GBT / 8939-2018 Sanitary Napkin Pads. Place the standard test module on top of the sample;
[0082] 3. Use a pipette to put 5 ml of pig blood into the standard test module, and start timing the time required for the pig blood to be completely absorbed by the surface layer (i.e., absorption time s);
[0083] 4. After 5 minutes, cover the liquid adding point with filter paper (diameter 110mm) of known weight and place a 2.5kg arc-shaped pressure block (consistent with the arc of the standard test module) on it. After 2 minutes, weigh the weight W2 of the filter paper and calculate the increased weight of the filter paper (i.e. the back-seepage amount W).
[0084] 5. Test the diffusion length of the surface layer and the core.
[0085]
[0086] Compared with comparative example 1, embodiment 1 has faster absorption speed, smaller back seepage amount, smaller surface diffusion area, and larger core diffusion area. The pore structure of the low-pressure spunlace hot air diversion layer on the curved surface has good shape retention and obvious pore difference, ensuring that the surface liquid quickly infiltrates and is diffused and absorbed in the core.
[0087] Compared with Example 3, Example 1 has a faster absorption speed, a smaller back permeation amount, a smaller surface diffusion area, and a larger core diffusion area. In Example 3, no ultrafine denier fiber is added to the guide layer, and the diffusion effect is slightly poor. The low-pressure spunlace hot air guide layer can reasonably regulate the competitive relationship between liquid penetration and diffusion in the guide layer, so that the liquid can quickly penetrate the surface of the guide layer and diffuse rapidly in the bottom layer.
[0088] Example 2
[0089] The guide layer material of the present embodiment, which is a combination of low-pressure water spunlace and hot air, is prepared by a low-pressure water spunlace and hot air composite process, such as Figure 1 As shown, the specific process is as follows:
[0090] (1) Non-use surface fiber web: The non-use surface fiber web is opened, combed and laid, and the non-use surface fibers are laid directly.
[0091] The fiber web on the non-use side is laid straight to ensure a high degree of longitudinal orientation of the fibers, and the fibers are more compact, which is more conducive to longitudinal diffusion. The fiber web on the use side is opened and combed, and the fibers are sparsely arranged.
[0092] (2) Pre-hydroentanglement reinforcement of non-use surface fibers. Hydroentanglement reinforcement adopts the rotary drum entanglement process. The non-use surface fiber web is pre-wetted under the net curtain transportation and then undergoes pre-hydroentanglement reinforcement. The first hydroentanglement process is equipped with two hydroentanglement heads. The first hydroentanglement head is for front-side reinforcement, and the hydroentanglement head pressure is 15 bar; the second hydroentanglement head is for reverse-side reinforcement, and the hydroentanglement head pressure is 20 bar.
[0093] The water jet head used in the first water jet process consists of a main body, a water jet plate and a bottom cover, as shown in the figure. The bottom cover is a hollow structure, and a protruding conical injection hole is provided on the lower surface of the bottom cover, and the hollow bottom cover is connected to the injection hole. In this embodiment, low-pressure water jet is used, and the strength requirement of the cover plate is lower. The hollow structure of the cover plate can also meet the water jet requirements. The conical injection holes are linearly distributed on the lower surface of the bottom cover. The water jet plate is located at the center of the bottom cover, and the holes of the water jet plate are linearly distributed, arranged in parallel with the conical injection holes and distributed alternately. The aperture of the conical injection hole is about 1-5 times that of the water jet plate, and the distance from the net curtain is closer. While the water jet is reinforced, a high-pressure airflow is generated by the air source and enters the conical injection hole from the hollow bottom cover, forming a reinforcement airflow to impact the fiber surface. The air pressure of the conical injection hole is 10bar-40bar. The second water jet process does not require the use of airflow to assist reinforcement.
[0094] The kinetic energy of airflow is short-lived and easily dissipated. Although the reinforcement effect is relatively general, the material is fluffy after reinforcement and more hairiness will form on the surface, but the characteristic of airflow being easy to dissipate allows fine denier viscose fibers to move greatly and at large angles, causing the fiber orientation to change. The kinetic energy of water needles is maintained for a long time, and the energy is concentrated, which has little effect on the fiber orientation. The fibers are tightly entangled, which is more conducive to the formation of a dense pore structure. The fiber web is reinforced by alternating distribution of airflow and water needles, and alternating fluffy entangled areas and tightly entangled areas will be formed along the width direction of the material. The fluffy entangled area structure of the bottom layer is fluffy and hairy. When compounding, the hairiness will extend to the inside of the fiber web on the use surface and entangle with it, which can improve the sudden change in the pore diameter from the use surface to the non-use surface, thereby forming more transitional pore structures and improving the problem of slow absorption. At the same time, the orientation of the fibers along the width direction of the material changes to a structure of alternating random distribution and longitudinal distribution. The longitudinal distribution of fibers can make the liquid diffuse better in the longitudinal direction, but the longitudinal distribution of fibers has fewer entanglement points and the capillary effect decays faster; the random distribution of fibers has more entanglements and stronger capillary effect, but the diffusion has no directionality. The alternating structure of random distribution and longitudinal distribution not only has good longitudinal diffusion, but also increases the entanglement points, greatly improving the diffusion performance of the bottom layer.
[0095] The retained water in the fiber web will produce resistance and affect the effect of hydroentanglement, but it has little effect on the reinforcement effect of high-pressure water injection (100 bar or above can be called high-pressure water injection). The kinetic energy of low-pressure water injection is low, and the resistance caused by the retained water affects the reinforcement effect. For low-pressure hydroentanglement, the pressure roller device can remove the retained water to improve the consolidation effect of low-pressure hydroentanglement.
[0096] The mesh curtain plays a role in supporting the fiber web during the hydroentanglement, and at the same time, the reflected energy of the water needle further strengthens the fiber web, forming a denser mesh structure. The non-use surface fiber web adopts a high-mesh mesh curtain structure, which allows the fiber web to absorb more positive water needle energy and fully utilize the reflected water needle energy, making the fiber entanglement tighter.
[0097] Through the energy of the water needle, the orange-peel-shaped two-component fiber achieves preliminary fiber opening, and certain gaps will be generated between the different components in the fiber, which is more conducive to the subsequent alkaline solution entering the fiber and improving the subsequent fiber opening effect.
[0098] (3) Alkali treatment of the non-use surface fiber layer. After the first hydroentanglement, the fiber web is treated in an alkaline solution and then washed. The concentration of the alkaline solution is 4-6g / L, the bath ratio is 1:20-1:30, and the temperature is 40-80°C. Alkali treatment has two main functions: 1. Weaken the strength of the interface between the orange segment type two components and improve the subsequent fiber opening effect. The ester bond undergoes a hydrolysis reaction when encountering the alkaline solution, which corrodes the interface of the composite fiber and weakens the interface bonding strength; 2. Reduce the crystallinity of cellulose in the hygroscopic non-hot-melt fiber, increase the amorphous area in the fiber, improve the fiber's liquid absorption capacity, and increase the fine effect of the non-use surface hair.
[0099] (4) Second hydroentanglement. The non-use surface fiber web that has been treated with alkali and washed with water and the use surface fiber web are jointly subjected to the post-hydroentanglement reinforcement under the support of the mesh curtain. The fiber web on the non-use surface does not need to be pre-wetted. The upper fiber web and the lower fiber web are jointly subjected to the second hydroentanglement reinforcement under the support of the mesh curtain 2. The mesh curtain 2 is a 10-mesh mesh curtain. The second hydroentanglement process is equipped with two hydroentanglement heads with a pressure of 30 bar and 40 bar, and both are equipped with a pressure roller to remove the retained water in the fiber web. It is used for the fiber opening of the orange-slice type bicomponent fiber on the non-use surface and the compounding of the two-layer fiber web.
[0100] After the first water spunlace and alkali treatment, the composite interface force of the pie-shaped fiber is weakened, and then through the subsequent water injection, 20% to 40% of the pie-shaped fiber will be split into ultra-fine denier fibers, so that more pores of 10-20 microns or less than 10 microns are formed between the fiber mesh. The remaining unsplit pie-shaped fibers contain a certain amount of low-melting-point PET, which are thermally bonded to each other in the subsequent hot air reinforcement to further enhance the strength of the pore structure.
[0101] The surface fiber net used is not pre-wetted and contains a certain amount of air, which has a certain degree of hindrance to the energy of the water needle. At the same time, the surface fiber used is relatively thick and has a large bending stiffness. After the subsequent water spunlace reinforcement, it can still maintain a fluffy pore structure.
[0102] The mesh curtain 2 used in the subsequent water spunlace is a low-mesh mesh curtain. The water needle can better penetrate the fiber web and is not easy to reflect, ensuring that the double-layer fiber web can be composited and the surface fiber remains fluffy.
[0103] (5) The surface fiber web is opened and combed, and there is no need to lay the web, and it can be directly atomized and hot-air consolidated.
[0104] The atomized finishing liquid is composed of hydrophilic oil, adhesive and water. The atomized finishing mainly uses the atomizing device to split the finishing liquid into very small finishing droplets using high-speed airflow. The finishing droplets adhere to the lower surface of the fiber to achieve a single-sided finishing effect. The diameter of the finishing droplets is 0.001-0.1mm; the number is 10-1000 / cm 2 . In this embodiment, a holding hot air flow is provided between the atomizing device and the suction device. The holding hot air flow mainly has two functions: improving the atomization finishing efficiency; and increasing the viscosity of the finishing liquid. The holding air flow can ensure that the atomized droplets are evenly distributed on the surface of the fiber web on the use surface. In the process of the finishing droplets adhering to the fiber web, the holding air flow can gradually evaporate the water in the finishing droplets and increase the viscosity of the finishing droplets. When the finishing droplets with high surface tension and high viscosity are attached to the fiber web, most of the finishing liquid will adhere to the entanglement of the fibers, and due to the high viscosity, the droplets are changed from spherical to teardrop-shaped under the action of the suction device. When the infiltrating liquid contacts the solidified teardrop-shaped glue droplets, the Laplace pressure gradient difference caused by the change in curvature can accelerate the infiltration of the liquid.
[0105] The hydrophilic oil selected for the atomized liquid is mainly composed of a hydroxyl-modified organic silicone hydrophilic oil, and the adhesive is modified polyvinyl alcohol. The mass fractions of the hydrophilic oil and the adhesive are 5% and 2% respectively. The temperature of the holding airflow is set to 95-105°C, and the holding airflow pressure is 1-10 bar.
[0106] After entering the atomization finishing, the hot air oven is used for hot air consolidation. During the hot air consolidation, the airflow penetrates from the fiber web on the use side to the fiber web on the non-use side, and the fiber web on the non-use side is attached to the roller or mesh curtain. After hot air consolidation, it is rolled and cut to obtain the guide layer of the sanitary napkin. The drying temperature is 130-150℃, and the drying speed is 40m / min. For traditional hot air cloth, the hot air flow acts on the fiber web, causing the fiber displacement and hairiness. Due to the support of the roller or mesh curtain, the fiber hairiness on the side close to the roller or mesh curtain is less, and there are more consolidation points. After water spunlace and then hot air treatment, the non-use side is directly exposed to the water needle, while the use side is supported by the support net, and no hairiness will be generated on both sides; and water spunlace can create more contact points between fibers, forming more bonding points during subsequent hot air consolidation, thereby improving the pore strength.
[0107] Comparing the absorption performance of the guide layer and the performance of the sanitary napkin in Example 1 and Example 2, reinforcing the fiber web with alternating distribution of air flow and water needles can improve the sudden change in the pore diameter from the use surface to the non-use surface, thereby forming more transitional pore structures, and combined with the water droplet structure design, it can greatly improve the absorption speed of the guide layer and reduce the reverse osmosis amount.
[0108]
[0109]
[0110] Note: The maximum width of the core is 75.
[0111] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0112] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.
[0113] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A guide layer, characterized in that: The guide layer is composed of a double-layer fiber mesh, wherein: The weight of the guide layer is 30-60g / m 2 The non-use surface fiber mesh weight is 18-36g / m 2 The surface fiber mesh weight is 12-24g / m 2 ; The thickness of the guide layer is 0.8-1.6 mm, and the thickness ratio of the fiber mesh on the use surface to the fiber mesh on the non-use surface is 1:2-4; The non-use surface fibers are composed of bicomponent orange segment fibers and non-thermal-melting fibers with hygroscopicity.
2. The guide layer according to claim 1, characterized in that: The two-component orange-peel fiber is PA6 and low-melting-point PET, with a denier of 3D to 6D, a length of 10-50mm, a petal number of 6 to 32, and a fineness of 0.05-1D after fiber opening.
3. The guide layer according to claim 1, characterized in that: Water drop-shaped protrusions are formed on the lower surface of the fiber web on the use side and / or the fiber web on the non-use side. The diameter of the water drop-shaped protrusions is 0.001-0.1 mm. The number of the water drop-shaped protrusions is 10-1000 / cm 2 .
4. A process for preparing a guide layer, characterized in that: The process comprises the following steps: 1) Opening, combing and laying the fiber webs on the use side and the non-use side; wherein the fiber web on the non-use side is laid directly to ensure that the fiber longitudinal orientation is high and the fibers are more dense, which is conducive to longitudinal diffusion; 2) Perform two rounds of drum hydroentanglement reinforcement on the non-use surface fiber web. The pressure of the first and second hydroentanglement processes are 10-20 bar and 30-40 bar respectively, and each hydroentanglement process is equipped with 1-6 hydroentanglement heads; the mesh number of the drum mesh curtain 1 is 60-80 mesh, and the mesh curtain 2 is 10-30 mesh, and a pressing roller is provided after the hydroentanglement reinforcement to remove the retained water in the fiber web. 3) Alkali treatment of the non-use surface fiber layer.
5. The process for preparing the guide layer according to claim 4, characterized in that: The following steps are also included: Water drop-shaped protrusions are prepared on the lower surface of the fiber web on the use surface and / or the non-use surface, wherein the diameter of the water drop-shaped protrusions is 0.001-0.1 mm; and the number of the water drop-shaped protrusions is 10-1000 / cm 2 .
6. The process for preparing the guide layer according to claim 5, characterized in that: The step of preparing the water drop-shaped protrusions also includes: Atomized finishing liquid is prepared; the atomized finishing liquid consists of a hydrophilic oil agent, a binder and water. Using an atomizing device to spray droplets of atomized finishing liquid onto the surface of the fiber web; At the same time, the suction device is used to attach to the fiber surface to achieve a single-sided finishing effect; Using the hot air flow to change the viscosity of the atomized droplets is conducive to forming a water droplet structure; Hot air is used to pre-consolidate the fibers while allowing the atomized droplets to solidify on the fiber web surface in the form of water droplets.
7. A guide layer preparation system, characterized in that: The system at least includes a non-use surface fiber web preparation system; the non-use surface fiber web preparation system includes: a carding machine; a web laying machine; a first drum net curtain; a first water spunlace; a pressure roller; an alkali treatment device; a washing device; a second drum net curtain; a second water spunlace; an atomizing device; a holding airflow jet device; a suction device; and a hot air reinforcement oven; wherein, 1) The non-use surface fiber web is opened and combed by a carding machine; The net is laid by a net laying machine; The laid fiber web passes through the drum screen for the first hydroentanglement; After the first spunlacing process, the non-use surface fiber web is squeezed by a pressing roller and then enters the alkali treatment equipment; After the alkali treatment, the non-use surface fiber web is squeezed by a pressing roller and then enters the washing equipment; After washing, the non-use surface fiber web is squeezed by a pressure roller and passed through a rotary drum screen for the second hydroentanglement. 2) The surface fiber web is opened and combed, and there is no need to lay the web, and it can be directly atomized and hot-air consolidated; Use a surface fiber net to perform surface atomization through an atomization device; After being shaped by the holding air jet device and the suction device, it enters the hot air consolidation oven for consolidation; 3) Integrating the non-use surface fiber web processed in step 1) and the use surface fiber web processed in step 2).
Citation Information
Patent Citations
Composite flow guide material
CN104494244A
One-way moisture-conducting compound fabric, preparation method thereof and clothing
CN116353164A
Multi-layer composite non-woven material and preparation method and preparation system thereof
CN118721944A
Low back leakage's of quick water conservancy diversion hot -air non -woven fabric
CN208293206U
Opened nonwoven fabric
JP2000017554A